ANALISIS YURIDIS PENEGAKAN HUKUM TERHADAP PELAKU TINDAK PIDANA KORUPSI DANA DESA (STUDI PUTUSAN NOMOR 2/PID.SUS-TPK/2020/PT PLG) - Fikri Ramadhan, Mahzaniar (NERACA KEADILAN, 2024)
The purpose of this study is Law Enforcement against perpetrators of Village Fund Corruption, legal consequences for village heads who commit village fund corruption and how to prevent it, legal considerations of judges in passing decisions on village fund corruption by village heads in decision Number 2 / Pid.Sus-TPK / 2020 / PT Plg. The approach method used in this study is descriptive normative juridical, which is used to analyze laws and regulations and materials relevant to this study. The data sources used in this study are secondary data sourced from primary legal materials, secondary legal materials and tertiary legal materials. The data obtained are in the form of secondary data, so the data collection tool used is through library or literature searches. The results of the research and discussion show that law enforcement of corruption, the three components, namely substance, structure and culture, influence the implementation of law enforcement. The application stage of criminal law enforcement is a complex process, because it involves many parties (police, prosecutors, courts, correctional institutions, and legal advisors). Village officials who violate the prohibition will be subject to administrative sanctions in the form of verbal and/or written warnings. Furthermore, if administrative sanctions are not implemented, temporary suspension will be carried out and can be continued with dismissal. Law enforcement for Village Fund Corruption Crimes is carried out in two ways, namely preventive and repressive. With the provisions of the Corruption Law in this case, preventive action is taken because in carrying out their authority as law enforcement officers, they still often see facts in the field that Village Fund Corruption practices still occur. Therefore, criminal sanctions are imposed in accordance with Article 2 of the Corruption Law and can be temporarily suspended or dishonorably dismissed. The application of the law of Decision Number 2/Pid.Sus-TPK/2020/PT Plg has been appropriate and the defendant's actions have fulfilled the elements of the crime as the primary indictment chosen by the Panel of Judges which stated that the Defendant was proven guilty of committing the Criminal Act of Village Fund Corruption.